2022
DOI: 10.2147/ijwh.s355156
|View full text |Cite|
|
Sign up to set email alerts
|

Predictive Value of Serum Cholic Acid and Lithocholic Acid for the Diagnosis in an Intrahepatic Cholestasis of Pregnancy Population with High Levels of Total Bile Acids and the Correlation with Placental Hypoxia-Inducible Factor-1α

Abstract: Objective This study aimed to investigate the ability of serum cholic acid (CA) and lithocholic acid (LCA) in the diagnosis and perinatal prognosis assessment of intrahepatic cholestasis of pregnancy (ICP), and the relationship between both indicators and hypoxia-inducible factor-1α (HIF-1α). Methods Between March 2020 and March 2021, pregnant women with high levels of total bile acid (TBA) in the late pregnancy with TBA ≥10 μmol/L and TBA <10 μmol/L (control group) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Cholic acid (CA), a major primary bile acid, is the principal toxic bile acid species. Serum TBA profiles showed that elevated serum TBA was dominated by CA in patients with gestational cholestasis 9 . Studies of both animals and humans demonstrated that ursodeoxycholic acid (UDCA) treatment rescued ICP‐induced adverse pregnancy events via decreasing serum CA levels 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholic acid (CA), a major primary bile acid, is the principal toxic bile acid species. Serum TBA profiles showed that elevated serum TBA was dominated by CA in patients with gestational cholestasis 9 . Studies of both animals and humans demonstrated that ursodeoxycholic acid (UDCA) treatment rescued ICP‐induced adverse pregnancy events via decreasing serum CA levels 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Serum TBA profiles showed that elevated serum TBA was dominated by CA in patients with gestational cholestasis. 9 Studies of both animals and humans demonstrated that ursodeoxycholic acid (UDCA) treatment rescued ICP-induced adverse pregnancy events via decreasing serum CA levels. 10 Indeed, CA-induced cholestasis as animal models for ICP has been well established in rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, a substantial proportion of pregnant women with TBA levels equal to or exceeding 10 μmol/L may exhibit no clinical indications of ICP during their medical evaluations. [ 10 ] Consequently, the identification of potential predictors capable of diagnosing ICP before clinical symptoms manifest is of paramount importance.…”
Section: Introductionmentioning
confidence: 99%